The Distributions of Vocational High School Teachers’ Advanced Digital Competence (ADC) - Rahmawati, Sherly; Abdullah, Ade Gafar; Widiaty, Isma (Journal of Technical Education and Training, 2022)
Digital competence is one of the significant skills to be possessed by the teachers as the impact of rapid technology development in many aspects such as economy, education, health, and environment. Various digital competence measurements and frameworks had been developed to ensure that someone has an advance digital skill and one of those is DigComp 2.1 by European Commission. Many previous studies had been studied about teachers’ digital competence levels influenced by some factors such as age, gender, working period, and educational background. However, it is infrequently analysed that the advance digital competence (ADC) of Vocational High School (VHS) teachers is differentiated by engineering field and non-engineering field, area or region and its school quality. Moreover, this study aimed: (a) to show the ADC level analysis between VHS teachers in engineering and non-engineering school, (b) to delineate the ADC level of VHS teachers based on the islands where the school is located, and (c) to represent the impact of school quality towards the VHS teachers’ ADC level. The data was analysed using a quantitative approach with a descriptive statistics method. Additionally, the instruments of the survey to collect the data were adapted from the DigCompEdu framework in part of advanced level and measured using Likert scale. The participants of this study were 392 respondents but, it was classified and divided into some fields based on VHS fields, islands and school accreditation. The result of this study expounded that VHS teachers in the engineering field have higher scores at the ADC level even though there are some ADC components that should be upgraded by the VHS teachers in both fields. Meanwhile, islands and school accreditation had no significant impact yet showed the opposite result.